Structured educational app in improving self-care management in diabetes mellitus patients: systematic review - Karingga, Devangga Darma; Efendi, Ferry; Indarwati, Retno; Bushy, Angeline (International Journal of Public Health Science (IJPHS), 2023)
Self-care management is a process that does not only develop over time but evolves along with the experience of the type of illness. Successful self-management of diabetes mellitus depends on self-care motivation and self-awareness, specifically designed to control symptoms and avoid complications. This systematic review uses telehealth intervention and smartphone-based applications for diabetes mellitus patients with randomized control trial, qualitative, and cross-sectional studies obtained from six databases. This review included inclusion and exclusion criteria established using population, intervention, comparison, outcomes and study (PICOS) framework, and then data were extracted, reviewed, and assessed using the Joanna Briggs Institute (JBI) tool. Seventeen selected articles that met the inclusion and exclusion criteria passed the selection through the selection process shown in the flow chart, which all research results show an impact on self-care management. The use of technology especially the applications, is very influential and effective in increasing knowledge and self-care management of diabetes mellitus patients. Besides that, it can also save operational costs in providing interventions for people with diabetes mellitus, but further research is needed to look at the sustainability of structured educational applications on health outcomes.